3D printing of TPMS structural ZnO ceramics with good mechanical properties. Issue 9 (1st May 2021) - Lu, Jiaxiong; Dong, Peng; Zhao, Yongtao; Zhao, Yan; Zeng, Yong
Abstract: In this study, ZnO ceramics with two types of TPMS structure (Gyroid structure and Schwartz P structure) were fabricated by 3D printing. The solid content of ZnO ceramics powder was 38 wt%. The solid content of SR454NS Acrylic was 57 wt%. The other components of the slurry were photoinitiator, dispersant and sintering additive. The ZnO ceramics with high densification could be achieved after sintering at 1250 °C for 2 h. The average grain size was 37 μm and the true density of the printed ZnO ceramics was 4.95 g/cm 3 . The shape of printed ZnO ceramics can be controlled and the minimum size of thin rod is 200 μm. The compressive strength for Gyroid structural ZnO ceramic with 55% porosity and the Schwartz P structural ZnO ceramic was approximately 6.87 MPa and 4.02 MPa, respectively. The result shows that the Gyroid structural ZnO ceramics can bear much more deformation than the Schwartz P structure during the compression tests. The TPMS structural ZnO ceramics can be used in the field of sensing and detection in the future.